Enhancing Molecular Modelling Skill of High Schools Chemistry Teacher using Computational Chemistry Training - Andrian Saputra; Lisa Tania (Bulletin of Social Studies and Community Development, 2023)
Abstract: Current developments in information and communication technology require innovative efforts to integrate computers and visualization in learning. In the field of chemistry, many studies have proven that the integration of ICT plays a significant role in increasing the effectiveness of chemistry learning. The aim of this workshop activity is to increase the knowledge and skills of high school/MA chemistry teachers in Lampung Province in teaching atomic structure and chemical bonding based on computational chemistry using computational chemistry applications. This activity will be carried out for 6 months and will be attended by high school/MA chemistry teachers in Lampung Province. The training methods that will be used are workshops and guided practice. The activity evaluation design was carried out in 2 ways, namely evaluating participant understanding and evaluating participant skills. Evaluation of participants' understanding is based on pretest scores at the beginning of the activity and posttest at the end of the activity. Evaluation of participant skills is based on the participant performance assessment criteria during the workshop process. The results of the service implementation show that participants have been able to understand and know the types, advantages, functions and working/working procedures of smartphone-based molecular modeling applications for learning chemistry on atomic structure and the periodic system of elements. The participant performance during the training increase significantly in operating the computational program. The follow-up to this service is to expand the service participants to all teachers in Lampung Province and expand the workshop material not only on atomic structure and the periodic system of elements, but on other material such as chemical bonds, reaction rates, equilibrium, and so on. Keywords: computational chemistry training, molecular modelling skill, high school teacher.